Anomalous resistance and its effect on neutron yield production in Mather type dense plasma focus devices - A., Singh; S.S., Heoh; L., Sing (2022)
Fusion energy as a source of sustainable energy is a topic of much interest. The creation of fusion energy and neutron yield during pinching is studied in this paper with the aid of dense plasma focus machine and the Lee codes. Three different dense plasma machines namely PF 400, DPF 2.2 and India's- Assam plasma focus machine is studied by analysing the current waveforms. It was found that in machines with regular current dip, most of the fusion energy and neutron yield is released during the pinching process, whereas those with extended dip, the remnant inductive energy transferred to the instabilities releases extra neutrons and energy from the magnetic field after the normal pinch.